STRANGULATED LEFT BOCHDALEK DIAPHRAGMATIC HERNIA: A LESSON LEARNED - Soomro, Sirajuddin; Mahtam, Ishrat; Abbasi, Baqa Muhammad; Dodani, Menghraj (Journal of Ayub Medical College Abbottabad, 2022)
Congenital Bochdalek diaphragmatic hernia (CDH) is the most common embryologic defect of the diaphragm which occurs 1 in 2500-5000 live births. Most commonly CDH presents soon after birth but it can present late in 10-30% of cases, leading to a diagnostic dilemma. Late presenting patients can remain asymptomatic for a variable period before presenting with complications in the form of obstruction or strangulation of gut. Bochdalek diaphragmatic hernia presenting with strangulation of gut is very rare. We report a case of such a rare variety of strangulated Bochdalek left diaphragmatic hernia in an 11-month-old boy which was managed successfully.